Precision medicine in lupus nephritis: can biomarkers get us there? - Caster, Dawn J. (Transl Res, 2018)
Patients with systemic lupus erythematosus (SLE) frequently develop lupus nephritis (LN), a condition that can lead to end stage kidney disease (ESKD). Multiple serum and urine biomarkers for LN have been proposed in recent years, yet none have become incorporated into clinical use. The majority of studies have been single center with significant variability in cohorts, assays, and sample storage, leading to inconclusive results. It has become clear that no single biomarker is likely to be sufficient to diagnose LN, identify flares, and define the response to therapy and prognosis. A more likely scenario is a panel of urine, serum, tissue, and genetic biomarkers. In this review we summarize traditional and novel biomarkers and discuss how they may be utilized in order to bring precision medicine to clinical practice in LN.